2012
DOI: 10.1186/1745-6215-13-96
|View full text |Cite
|
Sign up to set email alerts
|

A community mobilisation intervention to prevent violence against women and reduce HIV/AIDS risk in Kampala, Uganda (the SASA! Study): study protocol for a cluster randomised controlled trial

Abstract: BackgroundGender based violence, including violence by an intimate partner, is a major global human rights and public health problem, with important connections with HIV risk. Indeed, the elimination of sexual and gender based violence is a core pillar of HIV prevention for UNAIDS. Integrated strategies to address the gender norms, relations and inequities that underlie both violence against women and HIV/AIDS are needed. However there is limited evidence about the potential impact of different intervention mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 46 publications
2
78
0
Order By: Relevance
“…Study, a pair-matched cluster randomised controlled trial, who listed out appropriate actions that were encouraged by the intervention. 23 Primary prevention activities raise expectations and as a result community members identify and inform about cases where women are facing violence in their homes without taking the consent of that woman. Our thrust on eliciting community member's participation and contribution has led to difficulties in maintaining confidentiality of the case.…”
Section: Being There For the Community: Immediate Crisis Responsementioning
confidence: 99%
“…Study, a pair-matched cluster randomised controlled trial, who listed out appropriate actions that were encouraged by the intervention. 23 Primary prevention activities raise expectations and as a result community members identify and inform about cases where women are facing violence in their homes without taking the consent of that woman. Our thrust on eliciting community member's participation and contribution has led to difficulties in maintaining confidentiality of the case.…”
Section: Being There For the Community: Immediate Crisis Responsementioning
confidence: 99%
“…A rigorous evaluation indicated that SASA! generated significant shifts in gender norms related to IPV, and found a 52% reduction in past-year experience of physical IPV among women (Abramsky et al 2012;Kyegombe et al 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Interventions responding to IPV have traditionally sought to establish support services for victims and improve the criminal and health sector responses (Abramsky et al 2012), Yet, there has been a more recent emphasis on interventions that prevent IPV. A promising IPV prevention approach is participatory group education to support individuals to identify the risk factors and consequences of IPV, and gain self-efficacy to prevent and respond to IPV (Campbell et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations